Reflexive monitoring for sustainable transformations: A game-based workshop methodology for participatory learning - Sara Lupini; Giovanna Bertella; Xavier Font (Annals of Tourism Research Empirical Insights)
In this study, we combined reflexive monitoring—a critical assessment, evaluation, and practice-adjustment process—with participatory learning through educational games to advance transformative sustainable tourism methodologies. The methodology was tested in a workshop with tourism practitioners in Norway. Using a constructivist lens, we analysed the narratives participants shared via game artefacts, observations, and debriefings. The tourism practitioners demonstrated some signs of enhanced reflexivity, trust, innovation, inclusivity, and equity, which contributed to their collective agency for sustainability. Integrating reflexive monitoring can empower practitioners to critically assess their practices, envision alternatives, navigate sustainability complexities, and drive transformative actions. Although further testing is required, the methodology holds promise for promoting sustainable tourism practices and enhancing practitioners' skills.